1998
DOI: 10.1128/mcb.18.4.2406
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear Matrix Protein Interacts with the Phosphorylated C-Terminal Domain of RNA Polymerase II

Abstract: Yeast two-hybrid screening has led to the identification of a family of proteins that interact with the repetitive C-terminal repeat domain (CTD) of RNA polymerase II (A. Yuryev et al., Proc. Natl. Acad. Sci. USA 93: [6975][6976][6977][6978][6979][6980] 1996). In addition to serine/arginine-rich SR motifs, the SCAFs (SR-like CTD-associated factors) contain discrete CTD-interacting domains. In this paper, we show that the CTD-interacting domain of SCAF8 specifically binds CTD molecules phosphorylated on serines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 85 publications
3
76
0
1
Order By: Relevance
“…Nrd1 has been reported to associate with the CTD in a yeast two-hybrid assay (7), and recent genetic evidence supports this finding (27). Likewise, a member of the rat SR (serine-arginine-rich)-like CTD-associated factor family, SCAF8 (previously known as rA8) has been shown to bind to the CTD by both genetic and biochemical experiments (7,28). Whereas the sequence homology shared by Pcf11p with the above two proteins is confined to the CTD-binding domain, extensive similarity with all of the other hypothetical proteins shown in the alignment is exhibited (Fig.…”
Section: Ctdmentioning
confidence: 96%
See 2 more Smart Citations
“…Nrd1 has been reported to associate with the CTD in a yeast two-hybrid assay (7), and recent genetic evidence supports this finding (27). Likewise, a member of the rat SR (serine-arginine-rich)-like CTD-associated factor family, SCAF8 (previously known as rA8) has been shown to bind to the CTD by both genetic and biochemical experiments (7,28). Whereas the sequence homology shared by Pcf11p with the above two proteins is confined to the CTD-binding domain, extensive similarity with all of the other hypothetical proteins shown in the alignment is exhibited (Fig.…”
Section: Ctdmentioning
confidence: 96%
“…Neither Clp1p (21) nor Pcf11p displays any similarity to known mammalian processing factors. However, Pcf11p does contain a putative CTD-binding domain at the N terminus that is homologous to domains found in a number of polypeptides from various organisms (26)(27)(28).Previous studies in our laboratory have revealed that subunits of CF IA are directly involved in transcription termination: Birse et al (29) demonstrated that mutations in RNA15, RNA14, and PCF11 affect transcription termination based on transcription run-on analysis. Exactly how these factors affect transcriptional termination has yet to be elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if there are regions that escape X inactivation during spermatogenesis, we used an antibody for the phosphorylated form of RNA polymerase II at serine 2 which is only present in transcriptionally active chromatin. 17,28,29 We found RNA polymerase II to be excluded from the XY body at pachytene, except for several discrete regions (Fig. 5B).…”
Section: Several Regions Escape X and Y Inactivation During Spermatogmentioning
confidence: 97%
“…Enfin, notons que la protéine SCAF8 semble interagir spécifiquement avec le domaine CTD phosphorylé. Des travaux de localisation démontrent clairement que la protéine se retrouve au site de transcription [26]. Toutes ces données appuient le rôle des protéines SCAF dans l'établissement de liens entre la transcription et l'épissage.…”
Section: Relation Existant Entre La Transcription Et La Maturation Deunclassified